2021
DOI: 10.1177/23743735211039328
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Treatment During COVID-19: A Qualitative Analysis of Patient-Perceived Risks and Experiences with Virtual Care

Abstract: During the COVID-19 pandemic, most cancer centers shifted from in-person to virtual cancer care to curb community spread and ensure care continuity. This qualitative descriptive study aimed to understand cancer patient-perceived risks related to COVID-19 and cancer treatment, as well as the patient-perceived and experienced value of virtual care. From June to August 2020, focus groups were conducted with patients under active management or observation for a diagnosed malignancy in Toronto, Canada. A thematic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 42 publications
1
38
0
Order By: Relevance
“…Some studies found that patients’ overall satisfaction with telehealth is high [ 9 , 10 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Reducing exposure to COVID-19 [ 15 , 22 ], including the time- and money-saving benefits of telehealth, promotes telehealth visits as a favorable option during the pandemic [ 10 , 16 , 17 , 20 , 22 , 23 , 24 , 43 , 44 ]. Despite its benefits, some patients felt that telehealth is not a good alternative to in-person visits because it does not optimize patients’ experience (e.g., no physical examinations) (43,44), and may compromise clinician-patient relationship, cybersecurity, and health care accessibility [ 12 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some studies found that patients’ overall satisfaction with telehealth is high [ 9 , 10 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Reducing exposure to COVID-19 [ 15 , 22 ], including the time- and money-saving benefits of telehealth, promotes telehealth visits as a favorable option during the pandemic [ 10 , 16 , 17 , 20 , 22 , 23 , 24 , 43 , 44 ]. Despite its benefits, some patients felt that telehealth is not a good alternative to in-person visits because it does not optimize patients’ experience (e.g., no physical examinations) (43,44), and may compromise clinician-patient relationship, cybersecurity, and health care accessibility [ 12 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other sociodemographic factors such as race, age, culture, and immigration status have been shown to influence patients’ ability to have successful telehealth appointments, which in turn can worsen patients’ access to health services [ 9 , 25 , 27 , 46 ]. Previous studies have shown that during the pandemic, patients who were older, had shorter treatment duration, identified as a visible minority, were foreign born, were in linguistic isolation, or had recently immigrated had lower preferences for receiving telehealth for their cancer care [ 9 , 13 , 15 , 18 , 24 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations